Dental erosion and its clinical management - Amaechi, Bennett T. (Springer International Publishing : Imprint: Springer, 2015)
Dental erosion adversely affects the aesthetics, function, and longevity of the dentition of adults and children alike, and its increasing incidence and prevalence are the source of growing concern. In response, many studies have been conducted on the condition during the past two decades, giving rise to diverse evidence-based management and prevention strategies. Familiarity with these strategies, and also with etiological and risk factors, is necessary for all professionals who work in dentistry and related health care. In this handbook, the most up-to-date theoretical and practical information on dental erosion is distilled into an accessible, practical, and clinically focused format. Topics are covered in a step-by-step, easy-to-understand manner, with tables, checklists, images, flowcharts, and bullet point-like presentation of core messages that is ideal for busy dental practitioners and students. Procedures and products not yet supported with evidence are not included. Besides providing evidence-based guidance on the varied treatment and prevention strategies, the book examines thoroughly the dental erosion process itself and the intrinsic and extrinsic causes. In addition, careful attention is paid to the etiology, prevalence, and management of dentin hypersensitivity, the restoration of worn dentin, and non-carious cervical lesions. The authors are renowned, clinically active international experts in different aspects of dental erosion and its management, and the book will be invaluable for general dental practitioners, dental students, dental educators, and other health professionals.